Mechanisms and rejuvenation strategies for aged hematopoietic stem cells - Li, Xia; Zeng, Xiangjun; Xu, Yulin; Wang, Binsheng; Zhao, Yanmin; Lai, Xiaoyu; Qian, Pengxu; Huang, He (Journal of hematology and oncology, 2020)
Hematopoietic stem cell (HSC) aging, which is accompanied by reduced self-renewal ability, impaired homing, myeloid-biased differentiation, and other defects in hematopoietic reconstitution function, is a hot topic in stem cell research. Although the number of HSCs increases with age in both mice and humans, the increase cannot compensate for the defects of aged HSCs. Many studies have been performed from various perspectives to illustrate the potential mechanisms of HSC aging; however, the detailed molecular mechanisms remain unclear, blocking further exploration of aged HSC rejuvenation. To determine how aged HSC defects occur, we provide an overview of differences in the hallmarks, signaling pathways, and epigenetics of young and aged HSCs as well as of the bone marrow niche wherein HSCs reside. Notably, we summarize the very recent studies which dissect HSC aging at the single-cell level. Furthermore, we review the promising strategies for rejuvenating aged HSC functions. Considering that the incidence of many hematological malignancies is strongly associated with age, our HSC aging review delineates the association between functional changes and molecular mechanisms and may have significant clinical relevance.